Quantification of Epileptogenic Network From Stereo EEG Recordings Using Epileptogenicity Ranking Method - Parasuram, Harilal; Gopinath, Siby; Pillai, Ashok; Diwakar, Shyam; Kumar, Anand (Frontiers in Neurology, 2021)
Precise localization of the epileptogenic zone is very essential for the success of epilepsy surgery. Epileptogenicity index (EI) computationally estimates epileptogenicity of brain structures based on the temporal domain parameters and magnitude of ictal discharges. Although, this method works well in cases of mesial temporal lobe epilepsy and it showed reduced accuracy to localize the epileptogenic zone (EZ) in neocortical epilepsy with a definite threshold (EI value). To overcome this scenario, in this study, we propose Epileptogenicity Rank (ER), a modified method of EI for quantifying epileptogenicity among patients which are based on spatio-temporal properties of Stereo EEG (SEEG). Energy ratio during ictal discharges, the time of involvement and Euclidean distance between brain structures were used to compute the ER. Retrospectively, we localized the EZ for 33 patients (9 for mesial-temporal lobe epilepsy and 24 for neocortical epilepsy) and optimized the ER for accurate EZ localization using post-op MRI and surgery outcomes. Epileptic network estimation based on ER successfully differentiated brain regions involved in the seizure onset network from the propagation network. ER was calculated at multiple thresholds leading to an optimum value that differentiated the seizure onset from the propagation network. We observed that ER < 7.1 could localize the EZ in neocortical epilepsy with a sensitivity of 94.6% and specificity of 98.3% and ER < 7.3 in mesial temporal lobe epilepsy with the sensitivity of 95% and specificity of 98%. In non-seizure-free patients, the EZ localized the brain area beyond the cortical resections. Methods like ER can improve the accuracy of EZ localization for brain resection and increase the precision of minimally invasive surgery techniques (radio-frequency or laser ablation) by identifying the epileptic hubs where the lesion is extensive or in nonlesional cases. For inclusivity with other clinical applications, this ER method has to be studied on more patients.